Transgression as Tragic Typology: O’Neill’s Mourning Becomes Electra and Kushner’s Angels in America - Rendix, Mia (Academic Quarter | Akademisk kvarter, 2011)
We find a different way of using transgression in Mia Rendix’sarticle Transgression as Tragic Typology, where Rendix argues that American tragedy differs in kind from the European tragedy. American tragedy insists on a dual nature where cosmic harmony may be shattered and recreated through apocalyptic transgressions.